Utilisation of oil palm fronds as ruminant feed and its effect on fatty acid metabolism - Abdul Ghani, Ahmad Afifi; Rusli, Nor Dini; Shahudin, Muhammad Syafiq; Goh, Yong Meng; Saad, Mohd Zamri; Ahmad, Hafandi; Abu Hassim, Hasliza (Universiti Putra Malaysia Press, 2017)
Inclusion of oil palm fronds (OPF) pellets (200 g kg-1 DM) in a complete animal feed has been found to increase the unsaturated fatty acid content in ruminants. However, given the low-fat content of OPF (21 g kg-1 DM), changes in ruminal fatty acid (FA) metabolism will only result in nutritionally relevant differences in animal tissues when OPF enhances conservation of polyunsaturated fatty acid (PUFA) from external sources. Additionally, given the low metabolisable energy value (4.9 to 6.5 MJ (ME) kg-1 DM) of OPF, supplementation of OPF with an energy-dense feed compound such as fat is of interest. Thus, this approach could also be used in combination with other dietary fat supplementation strategies to further manipulate fatty acid concentration of ruminant tissues and products for human consumption.